Low-carbon heating solutions using road thermal collectors and seasonal energy storage in mediterranean climates - Stefania Guarino; Alessandro Buscemi; Marina Bonomolo; Marco Beccali; Valerio Lo Brano (Energy Conversion and Management: X, 2025)
The building sector accounts for 40% of final energy consumption and 36% of energy-related greenhouse gas emissions in Europe, positioning it as a critical target for decarbonisation under the European Green Deal. Road Thermal Collectors (RTCs), a type of heat-harvesting system, utilize urban surfaces like roads to capture solar energy for thermal applications. When combined with Borehole Thermal Energy Storage (BTES) and water-to-water heat pumps, RTCs provide a multifunctional, low-carbon heating solution while also mitigating urban heat island effects. This study investigates an RTC-BTES hybrid heating system in a school building in southern Italy, where t––he Mediterranean climate poses unique challenges and opportunities for seasonal thermal energy storage. The system’s performance is assessed through dynamic simulations using TRNSYS software, with RTC models validated against experimental data from the University of Palermo. A typical school with an annual heating demand of 166 MWh was analysed, comparing the performance of the proposed integrated heating system with one using conventional gas boilers. The results demonstrate that the integrated system significantly reduces primary energy consumption and CO2 emissions, offering a scalable and sustainable alternative to fossil fuel-based heating, advancing low-carbon solutions for non-residential buildings.